The impact of White Shark (Carcharodon carcharias) sightings and attacks on recreational water use patterns in False Bay - Engelbrecht, Tamlyn (Department of Biological Sciences, 2014)
White sharks (Carcharodon carcharias) are apex predators that play an important role in the structure and functioning of marine ecosystems. However, despite both their ecological importance and threatened conservation status this species is still subject to lethal control to reduce the risks of predation for recreational water users. The Shark Spotter program, pioneered in False Bay, South Africa, proposes a non-lethal alternative to reducing predation risk. This program aims to balance the needs of people with white shark conservation by actively reducing conflict between recreational water users and sharks. In this study I establish the extent of spatial overlap between white sharks and water users at two popular recreational beaches in False Bay (Fish Hoek and Muizenberg), and investigate how shark sightings (accompanied by warning flags and/or a siren) as well as attacks influence water use patterns amongst bathers, surfers and paddlers. In the period from 2006 to 2012, the total number of shark sightings recorded was 531 at Muizenberg and 322 at Fish Hoek, with a notable increase in sightings at both beaches in recent years. Shark sightings were rare in winter increasing into the spring and summer months when recreational use of the inshore was highest. Daily shark sightings peaked at midday to late afternoon at both beaches, coinciding with peak numbers of water users. The response of water users to warnings of shark presence by the Shark Spotters was only found to be significant in cases where the siren was sounded by the shark spotters, and in the absence of a siren warning flags had little impact on average numbers of water users. The occurrence of a fatal shark attack was found to a) increase response of water users to auditory warnings (when the siren is sounded) but not visual warnings (warning flags unaccompanied by a siren); and b) reduce the average number of water users present at both beaches for at least three months following the fatal incident. Annual averages of water users at Muizenberg beach also reflected this pattern, with a general reduction in water use in years with attacks compared to those without. These findings indicate that the Shark Spotter program is effective in mitigating conflict between water users and white sharks through auditory warnings and subsequent beach clearing in the event of a shark sighting; however the lack of response by water users in the absence of a siren and after long periods without an attack remains a challenge to the effectiveness of the program. The large spatial overlap between white sharks and water users, as well as the increasing number of shark sightings at both beaches, emphasises the need for continuous revision and improvement of mitigation strategies to prevent conflict between white sharks and water users in False Bay.